Mobile Application for Student Assessment with Android - Afriyudi, Afriyudi; Akbar, M. (Proceedings of KNASTIK, 2012)
Bina Darma University as university-based Information Technology has steppedforward in the vision and mission. One of example is the implementation of InformationTechnology in the academic process, such as the Academic Information Systems, andE-learning. This system would assist lecturers in teaching and learning activities suchas knowing the schedule of teaching, preparing teaching materials and conducting theonline grading. This applications will be built is an alternative application that allowslecture to assess student work offline by using the android platform. Previous researchhas been done by creating a desktop-based desktop applications with converting exceldata format that is used to input grade student and then the data will be sent to theacademic information system. In the process of development will be an android-basedapplication that allowss implification of the previous application. Applications thatwill be designed for the lecturer can make an offline assessment to students, a featurethat was added to the android app is student attendance records. The methods to beused in the development of this system is the system life cycle. The expected result is themobile-based application with android platform that can facilitate the entry process ofstudent grade and convert them to academic information system.